The Effect of Anti-Fatigue Mat and Stretching on Musculoskeletal Disorders (MSDs) Complaints of Sewing Operator PT. X - Dine Wahyu Prima; Yuliani Setyaningsih; Daru Lestantyo (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Musculoskeletal complaints are experienced by 1.71 billion people in the world, contributing to disability, pain and reducing work productivity. In Indonesia, the prevalence of MSDs is 11.9%, and the top position with 65.2% of cases was the garment sector. The garment sector generally applies a sitting posture, but at PT X all sewing operators work in a standing posture. Long-term standing poses a risk to health, muscles, skeleton and other body parts. To determine the effect of using anti-fatigue mats and stretching on MSDs complaints of sewing operators. Using a quasi-experiment by dividing the respondents into 4 groups. The total population is 156 sewing operators, and samples that meet the criteria are 112 people. Data analysis used paired T-test. There is no effect of stretching on the level of MSDs complaints (p-value = 0.745), there is no effect of using anti-fatigue mats on MSDs complaints (p-value = 0.326), and there is an effect of using anti-fatigue and stretching mats on MSDs complaints (p-value = 0.006). It is known that the combination of the use of anti-fatigue mats and stretching has an effect on MSDs complaints, the suggestion is all sewing operators can implement the program optimally and effectively every day.